CRAB Technology Platforms and CRAB Technology Based Smart Contracts. Benefits, Ways of Application, Legal Challenges and Future Development - Demchenko, Olena (Pécs journal of international and European law, 2018)
The present paper explains the role of the CRAB (Create, Retrieve, Append, Burn) technology platforms and CRAB technology-based smart contracts for modern governmental activity and private business - from commercial models based on decentralized applications to official registration services on governmental platforms, focusing on real-life examples worldwide, in order to understand possible ways of application of CRAB technology in global perspective. Current research examines in details the various applications of CRAB technology and analyses legal challenges arising with the widespread of CRAB technology-based smart contracts in the connection with already existing legal frames – digital currencies regulation, investment activity regulations, consumer protection or litigation and dispute resolution. Present paper analyses gaps in existing legal procedures, stresses on necessity of new legal models in order to regulate smart contract-based commercial activity and underlines the importance of amendments acceptance to current international legislation with the focus of new developments of CRAB technology smart contract platforms and decentralized applications to straighten the financial market, secure competition, protect consumers and investors.